2020
DOI: 10.1002/minf.202000203
|View full text |Cite
|
Sign up to set email alerts
|

Embedding of Molecular Structure Using Molecular Hypergraph Variational Autoencoder with Metric Learning

Abstract: Deep learning approaches are widely used to search molecular structures for a candidate drug/material. The basic approach in drug/material candidate structure discovery is to embed a relationship that holds between a molecular structure and the physical property into a low‐dimensional vector space (chemical space) and search for a candidate molecular structure in that space based on a desired physical property value. Deep learning simplifies the structure search by efficiently modeling the structure of the che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…The evaluation measures show significant and noticeable improvement with joint embedding. Previous works have shown that joint training leads to an organization of the data according to the prediction tasks, [25,27–29,36] and the present results appear to provide further support for this behavior. This has the effect presently of providing the observed clustering and continuity features of the latent space described above.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The evaluation measures show significant and noticeable improvement with joint embedding. Previous works have shown that joint training leads to an organization of the data according to the prediction tasks, [25,27–29,36] and the present results appear to provide further support for this behavior. This has the effect presently of providing the observed clustering and continuity features of the latent space described above.…”
Section: Resultssupporting
confidence: 87%
“…A recent discussion of joint training noted that it may fail to organize latent space dimensions not correlated with the jointly trained property and may result in the unwanted clustering of molecules with dissimilar structural features [36] . We note that our manual feature vector contains structure‐based properties many of which are uncorrelated.…”
Section: Methodsmentioning
confidence: 98%
“…Yan et al [30] propose a re-balancing VAE Loss to generate more valid SMILES molecules. [34] Generating graphs from a continuous representation in the latent space graph QM9 and ZINC Shervani-Tabar et al 2020 [35] Computing the statistics of molecular properties given small size training data set graph QM9 [38] A VAE-based masked graph model for molecular graphs graph QM9 and ChEMBL Koge et al 2020 [39] Molecular embedding learning that combines metric learning and VAEs graph QM9 Kwon et al 2020 [40] Generates compressed graph representation for scalable molecular graphs graph ChEMBL…”
Section: Figure 3 a Molecular Represented As A String Notation Callementioning
confidence: 99%
“…In addition to generating new molecules, there are also studies on representation learning for decision-making based on VAEs. Koge et al [39] proposed a method of molecular embedding learning using a combination of VAE and metric learning. This method can simultaneously maintain the consistency of the relationship between molecular structural features and physical properties, resulting in better predictions.…”
Section: Figure 3 a Molecular Represented As A String Notation Callementioning
confidence: 99%
See 1 more Smart Citation